2014
DOI: 10.1002/ejoc.201402741
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Total Synthesis of Klaivanolide: Complete Reinterpretation of Its Originally Assigned Structure

Abstract: Klaivanolide is an antiparasitic natural product isolated from Uvaria klaineana, whose structure was originally assigned as a seven‐membered lactone ring. Attempts towards the total synthesis of klaivanolide led us to revise its original structural assignment based on both experimental evidence and spectroscopic data. The isolated compound was revealed to be a known molecule, acetylmelodorinol, originally isolated from Melodorum fruticosum. Vibrational circular dichroism simulation of the reassigned structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
(26 reference statements)
2
11
0
Order By: Relevance
“…) . The QC simulated VCD spectrum of (7 S )‐acetylmelodorinol was also reported to agree with the experimental VCD spectra of the isolated compound …”
Section: Interpretational Approaches That Can Lead To the Wrong Pathsupporting
confidence: 72%
See 1 more Smart Citation
“…) . The QC simulated VCD spectrum of (7 S )‐acetylmelodorinol was also reported to agree with the experimental VCD spectra of the isolated compound …”
Section: Interpretational Approaches That Can Lead To the Wrong Pathsupporting
confidence: 72%
“…A few years later, it was reported that the isolated compound was not klaivanolide, but is a different compound, acetylmelodorinol (see Fig. ) . The QC simulated VCD spectrum of (7 S )‐acetylmelodorinol was also reported to agree with the experimental VCD spectra of the isolated compound …”
Section: Interpretational Approaches That Can Lead To the Wrong Pathmentioning
confidence: 56%
“…In the case of 8 , the original structure belonged to neosporol ( 8A ) and the revised structure to sporol ( 8B ). In the case of 9 , original structure belonged to klaivanolide ( 9A ) and the revised structure to acetylmelodorinol ( 9B ) . In each case, full conformational search was undertaken and Boltzmann population weighted VOA and EOA spectra were calculated for both correct and misassigned structures and their SSO analyzed (Figure , Figure and Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…VCD measurements on the corresponding alcohol molecule were hampered by its immediate racemization in CCl 4 , CDCl 3 , and CD 2 Cl 2 . VCD calculations [B3LYP/6-31G(d)] on the reassigned structure conrmed the absolute conguration at C7 as S. 173 The absolute conguration of (+)-cephalochromin (160), a homodimeric naphthopyranone containing both axial and central chirality was determined as aS,2R,2 0 R using a combination of OR, ECD, and VCD in conjunction with the corresponding quantum chemical predictions at the B3LYP/6-311G(d) level. 170 The chiral furanones (À)-sotolon (156) and (+)-maple furanone (157) had their absolute congurations assigned as R by comparing VCD experimental spectra with B3PW91/6-31G(d,p) calculated ones.…”
Section: Miscellaneousmentioning
confidence: 99%